Survey of Literature on Demand for Money : Theoretical and Empirical Work with Special Reference to Error-Correction Models - Sriram, Subramanian (Washington, D.C. : International Monetary Fund, 1999)
A stable money demand forms the cornerstone in formulating and conducting monetary policy. Consequently, numerous theoretical and empirical studies have been conducted in both industrial and developing countries to evaluate the determinants and the stability of the money demand function. This paper briefly reviews the theoretical work, tracing the contributions of several researchers beginning from the classical economists, and explains relevant empirical issues in modeling and estimating money demand functions. Notably, it summarizes the salient features of a number of recent studies that applied cointegration/error-correction models in the 1990s, and it features a bibliography to aid in research on demand for money.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet